Kontruksi Makna Mural Bagi Seniman Mural Di Kota Karawang - Munawwar, Ahmad Fuad; Abidin, Zainal; Utamidewi, Wahyu (Peneliti.net, 2023)
This study discusses the motives, meaning, and communication experiences of mural artists in Karawang. This study uses a qualitative research method with a phenomenological study, which is a research that focuses on the conscious experience of individuals. Phenomenology examines a reality of experience experienced by someone and that person also knows it. phenomenology as a guide in conducting research. The communication experience of seeing the various scribbles on the wall is related to the communication aspect in the form of the communication process, the resulting symbols and meanings. Therefore, the researcher focuses on the motives, meanings, and communication experiences of mural artists in making murals on the streets. The streets I mean are the walls and rolling doors of shops along Jalan Tuparev and also along Jalan Achmad Yani, Karawang. The method used in this study is a qualitative approach with phenomenological methods. Data collection techniques namely Observation, Interview, and Documentation. Data sources are primary data and secondary data. The subjects in this study were mural artists in Karawang.